Abbreviation as a Language Phenomenon in Self-Made Captions used by Teenagers on TikTok Social Media - Wibowo, Hanafi; Ningtyas, Melly Anggoro (Fakultas Sastra - Universitas Muslim Indonesia, 2024)
People often use TikTok to share their daily activities, interact with friends, do some business, and for educational goals such as share information, exchange their opinions, and runs a discussion. This research is driven by two primary objectives: first, to analyze the forms of English abbreviation words; second, to describe the reason why the teens use English abbreviation words in TikTok. This study used qualitative research with purposive sampling method, the study meticulously analyzed abbreviation words in tiktok by the teenagers collected from January to June 2024. The source of data of this research were words, phrase, and sentences in video and caption which people use in TikTok as the prime source. The writer also used the answers from the interview which is given to TikTok users around the world as the source. The data analyzed by using qualitative descriptive method with applying Bengtsson theory The findings of the study indicate that there were 120 English abbreviation words found and often used by the users from all the world. It found that there were five kinds of abbreviation words namely clipping word, initialism, acronym, contraction, and blend. Based on this study, it also found that people mostly use types of abbreviation through initialism. There are four reasons why people use English abbreviation words in TikTok, they are limited space to type, the need to type faster, follow the trend, and the presentation of typing.